RECOVERY SCIENCE DALAM OLAHRAGA: PENGARUH ICE BATH TERHADAP DELAYED ONSET MUSCLE SORENESS (DOMS) - Nimrot Manalu; Aqilah Ramadhani Parinduri; Harry Mustary Purba; Ingat Berkat Giawa; Titus Manik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Delayed Onset Muscle Soreness (DOMS) is a condition characterized by muscle pain and stiffness that commonly occurs after high-intensity exercise, especially activities involving eccentric muscle contractions. DOMS can reduce physical performance and delay muscle recovery after exercise. Therefore, an effective recovery method is needed to minimize muscle soreness and improve recovery. This study aimed to determine the effect of ice bath therapy on reducing DOMS after high-intensity exercise. The research used a quantitative approach with a quasi-experimental design through a pretest-posttest control group design. A total of 20 physically active participants were divided into an experimental group and a control group. The experimental group received ice bath treatment using water temperatures of 10–15°C for 10–15 minutes, while the control group performed passive recovery. DOMS levels were measured at 24, 48, and 72 hours after exercise using a pain scale instrument. Data analysis was conducted using descriptive and inferential statistics through an independent sample t-test at a significance level of 0.05. The results showed that the experimental group experienced a greater reduction in DOMS scores compared to the control group, especially at 48 and 72 hours post-exercise. Therefore, ice bath therapy is effective in reducing muscle soreness and accelerating recovery after high-intensity physical activity.